(untitled) (Journal of Informatics Education and Research, 2024)
In a Data-Driven World, Information Overload is Which Way Up! Navigating it is a Challenge Given the level of information that organizations are now expected to make fast, accurate, and insightful decisions on against; welcome to a world of data. Alongside others proactive solutions, from strategic innovations in data analytics about Artificial Intelligence (AI), and Machine Learning (ML). AI and ML are changing the very nature of decision-making and this paper reveals how organizations now have new possibilities to generate truly actionable insights from the complexities of big data. By automating data processing, AI & ML minimize human error and bias, accelerate decision making processes, and identify patterns previously undetected. This paper highlights artificial intelligence and machine learning in business strategy along with individual uses in the healthcare and finance industry, retail, and supply chain management. This concentrates on real-world uses of Ai-based analytics regarding enhanced customer experience, operational resource optimization predictions, and intelligent operational strategies. It also draws attention to the bottom-line benefits of using these technologies — increased profitability, lower costs and improved customer satisfaction — which companies must generate to remain competitive. It closes by presenting a blueprint for large-scale adoption of AI and ML analytics for businesses, highlighting various challenges and issues that need to be addressed which is complemented by a vision for the future of data-driven decision making.